An experimental investigation on productivity and performance of a new improved design portable asymmetrical solar still utilizing thermoelectric modules. (15th June 2016) - Rahbar, Nader; Esfahani, Javad Abolfazli; Asadi, Amin
Highlights: A novel asymmetrical solar still utilizing thermoelectric cooler has been designed. The productivity on TEC was 3.2 times greater than that of the glass. Using TEC causes the greater temperature difference compared to glass–water. The start point of distillation on TEC was earlier than that of the glass. Maximum daily productivity of the studied solar still was approximately 500 ml. Abstract: The present study is a continuation of the authors' previous investigations on productivity estimation of portable solar stills utilizing thermoelectric modules (Esfahani et al., 2011; Rahbar and Esfahani, 2012). In this study, a new improved design portable asymmetrical solar still has been designed, fabricated and tested over six typical summer days (between 27/08/2014 and 07/09/2014) under the real climatic conditions of Semnan (35°33′N, 53°23′E), Iran. The effect of thermoelectric cooler (TEC) on productivity and performance of the still has been experimentally investigated. The results declared that although the surface of TEC is approximately 2.8 times smaller than that of the glass, its productivity is 3.2 times greater. Furthermore, the start point of distillation on TEC was earlier than that of the glass by 3 h due to its lower temperature. The minimum and maximum daily productivity of the studied solar still was approximately 225 and 500 ml in the solar intensity of 20, 500 and 25, 500 J/m 2, respectively.